Interlayer coupling through a dimensionality-induced magnetic state - M. Gibert (Nature Portfolio, 2016)
Oxide materials can be combined to create heterostructures exhibiting complex properties not found in either substance individually. Here, the authors observe antiferromagnetic interlayer exchange coupling between ferromagnetic lanthanum manganite and nominally paramagnetic lanthanum nickel oxide.